Dinamika Hubungan Antara Mahkamah Agung Dan Mahkamah Konstitusi: Perspektif Konflik Dan Kolaborasi - Siregar, El Renova Ed; Prabandari, Adya Paramita (JURNAL USM LAW REVIEW, 2024)
This research aims to analyze the role of the Constitutional Court (MK) and the Supreme Court (MA) in the context of justice in Indonesia, with a focus on potential inconsistencies in objectives that may occur due to the delegation of authority to review Regional Regulations (Perda) to the Supreme Court. The background to the problem includes the division of duties between the Constitutional Court and the Supreme Court, as well as legal political dynamics that may influence the performance of the two institutions. The urgency of writing lies in the need to highlight the ambiguity of the Constitutional Court's objectives as guardian of the principles of the rule of law in the context of the existence of the Supreme Court which also has legal review authority. The research method used is normative juridical research, by analyzing various legal regulations and related Constitutional Court decisions. The novelty of the research lies in the latest review of political and legal dynamics in Indonesia. The research results show the need to improve the working mechanisms of the Constitutional Court and Supreme Court so that they are in accordance with their respective purposes, as well as maintaining consistency in carrying out their supervisory function over the constitutionality of law. Therefore, recommendations have been prepared to clarify the division of tasks between the two institutions in order to realize the principles of the rule of law more consistently and effectively.  Penelitian ini bertujuan untuk menganalisis peran Mahkamah Konstitusi (MK) dan Mahkamah Agung (MA) dalam konteks peradilan di Indonesia, dengan fokus pada potensi inkonsistensi tujuan yang mungkin terjadi akibat pelimpahan wewenang pengujian Peraturan Daerah (Perda) kepada MA. Latar belakang masalah meliputi pembagian tugas antara MK dan MA, serta dinamika politik hukum yang mungkin memengaruhi kinerja kedua lembaga tersebut. Urgensi penulisan terletak pada kebutuhan untuk menyoroti ambiguitas tujuan MK sebagai penjaga prinsip negara hukum dalam konteks keberadaan MA yang juga memiliki kewenangan pengujian hukum. Metode penelitian yang digunakan adalah penelitian yuridis normatif, dengan menganalisis berbagai peraturan hukum dan putusan-putusan MK terkait. Kebaharuan penelitian terletak pada tinjauan terbaru terkait dinamika politik dan hukum di Indonesia. Hasil penelitian menunjukkan perlunya penyempurnaan mekanisme kerja MK dan MA agar sesuai dengan peruntukkannya masing-masing, serta menjaga konsistensi dalam menjalankan fungsi pengawasan terhadap konstitusionalitas hukum. Oleh karena itu, disusun rekomendasi untuk memperjelas pembagian tugas antara kedua lembaga tersebut guna mewujudkan prinsip negara hukum secara lebih konsisten dan efektif.